PERSEPSI KEPALA SEKOLAH TERHADAP SISTEM DIGITALISASI PENGELOLAAN SEKOLAH DASAR DI SD EL FITRA - Ius Rusnati; Mohammad Fakry Gaffar; Aan Komariah; Dadang Suhardan; Sri Mulyani (Jurnal Al Burhan, 2021)
This study aims to find out the role of the principal in the utilization of digitalization system for elementary school management through SMSBK application at SD El Fitra, Bandung City. The method used in this study is the case study method. Based on the research findings, the results and impact of the implementation of the school management digitization system by the principal obtained an idea that the smsbk application implemented improves the quality of management, facilitates the control of unfinished work, accelerates the reporting process. In addition, this application is also able to help school management, improve teacher productivity and performance, and facilitate task completion because data is centralized in digital.